VISUAL IDENTITY DESIGN OF KANDRI VILLAGE AND ITS APPLICATION ON PROMOTION MEDIA - Meydiana, Meydiana (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The aim of this research is to produce a visual identity of logo and applied to some promotion media as needed, so that it can be increase the amount of tourists and it can be positioning the Desa Wisata Kandri as modern tourist village. Visual identity of logo and applied to some promotion media served in some of category, that is stationary set, coupon, brochure, X-banner, identity card, ticket, merchandise, display on social media and advertisement on social media. The process of visual identity design through a few steps of work with pre-production process sequence, production process, and post production process. With the design of visual identity hope that it can help Desa Wisata Kandri to develop their own image to audience, it can provide value-added and it will make Desa Wisata Kandri able to compete with all the competitor.